Effective Mixer Design an Important Factor In SSCR Systems for Reduction of NOx from Exhaust of Diesel Engines - M. K. Yadav and A. K. Srivastava (Nature Environment and Pollution Technology, 2022)
In recent decades, the environment has been seriously polluted by the hazardous exhaust components of diesel engines. The international community, which is dedicated to preserving the harmony between nature and humanity, has taken this seriously and imposed strict regulations on Diesel engine manufacturers regarding the quantity of exhaust components from Diesel engines that may apply to the standards of EURO-VI. The SCR technology attempted to reduce the problem somewhat, but the associated problems of solid particle formation on the pipe walls, ammonia slip, and incomplete NOx reduction led to the development of new technology - solid selective catalytic reduction. The use of solid ammonium salt for ammonia generation has shown better results in NOx reduction and reduction of solid particle formation compared to SCR. However, it was not possible to fully resolve the ammonia slip issue. A uniform flow rate of ammonia through the SCR catalyst can reduce NOx efficiently. In this paper, the role of mixer design in achieving a uniform flow rate of ammonia is investigated in detail. The results show that an optimized mixer design leads to efficient reduction of NOx and thus reduces ammonia slip to a great extent. When the mixer is placed near the ammonia injection point, the most homogeneous ammonia distribution is achieved for flow through the SCR catalyst.